2018
DOI: 10.1017/s0954579418000883
|View full text |Cite
|
Sign up to set email alerts
|

The course of maternal repetitive negative thinking at the transition to motherhood and early mother–infant interactions: Is there a link?

Abstract: Potential long-term associations between repetitive negative thinking and mother-infant interactions have received little attention. The current longitudinal study including N = 62 mother-infant dyads investigated both maternal and infant behavior in face-to-face interactions as a function of pre- and postnatal maternal repetitive negative thinking when infants were aged around 4 months. We hypothesised that mothers with a strong tendency to engage in repetitive negative thinking would react less contingently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In addition, primiparous women reported higher intrusive thoughts and dissociative experiences than multiparous women, highlighting the vulnerability of women in the transition to motherhood (Müller et al, 2019 ; Nelson et al, 2014 ). It may be assumed that the stress and difficulties involved in adjusting to their new role may cause first‐time mothers to feel more overwhelmed and anxious, leading to more intrusive thoughts related to infant care (Murray & Finn, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, primiparous women reported higher intrusive thoughts and dissociative experiences than multiparous women, highlighting the vulnerability of women in the transition to motherhood (Müller et al, 2019 ; Nelson et al, 2014 ). It may be assumed that the stress and difficulties involved in adjusting to their new role may cause first‐time mothers to feel more overwhelmed and anxious, leading to more intrusive thoughts related to infant care (Murray & Finn, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…More longitudinal investigations of the capacity of RNT to predict later symptom levels, assessed via studies in which RNT and psychological symptoms are sampled multiple times throughout the postnatal period, are needed. For example, Muller et al (2019) sampled RNT at multiple timepoints throughout pregnancy and postpartum, enabling examination of the trajectory of RNT, as well the opportunity to distinguish women who were consistently high versus consistently low in RNT throughout the perinatal period. More studies adopting such a design will enable us to better understand the course and predictive role of postnatal RNT.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Muller et al (2013) reported that antenatal RNT did not predict postpartum depression symptoms; however, the unproductive (but not repetitiveness) facets of antenatal RNT predicted impairments in mother-infant relationship (as reported by mothers) at 5 weeks postpartum. In another study, women with consistently high levels of RNT during both pregnancy and postpartum reported more depression and anxiety symptoms (Muller et al, 2019). In addition, infants with mothers with high levels of RNT spent more time examining their environment, and protested less frequently, relative to infants of low RNT mothers.…”
Section: Introductionmentioning
confidence: 94%
“…Capturing 2-min interactions optimizes the trade-off between the high validity of the data on one hand and minimal intrusion to post-partum women and their infants on the other hand. Accordingly, an experimental setup of 2-min mother-infant interactions is commonly applied 38,[123][124][125][128][129][130][131][132][133][134][135] . While short and thus susceptible to being affected by non-representative events, this data is rich in spontaneous interactive behaviors, providing a multi-dimensional matrix of 120 repeated data points per each behavioral variable for each dyadic partner.…”
Section: Methodsmentioning
confidence: 99%